2021
DOI: 10.21600/ijoks.827571
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Towards the First Language and Its Effects on First Language Lexical Attrition

Abstract: This paper presents an investigation into the relationship between individuals" attitudes towards their mother tongue and lexical attrition. The paper is based on data from a study wherein 10 Kurdish-Turkish bilinguals were asked to narrate a well-known story in their mother tongue of Kurdish. These individuals were selected from among 104 participants according to their score on the Mother Tongue Attitude Scale (MTAS), a scale used to determine attitude towards mother tongue.In this study, quantitative and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…As affective factors are a driving force of learning (Kasap & Peterson, 2018;Kasap, 2021), in order for the IEP process to be effective, teachers should have a positive attitude towards this application. Therefore, it is important to determine the attitudes of teachers towards the IEP process, who have a critical role in the IEP process.…”
Section: Introductionmentioning
confidence: 99%
“…As affective factors are a driving force of learning (Kasap & Peterson, 2018;Kasap, 2021), in order for the IEP process to be effective, teachers should have a positive attitude towards this application. Therefore, it is important to determine the attitudes of teachers towards the IEP process, who have a critical role in the IEP process.…”
Section: Introductionmentioning
confidence: 99%
“…Since emotional factors are the driving force of the learning process (Kasap & Peterson, 2018;Kasap, 2021), teachers need to adopt a positive attitude towards the IEP implementation process to implement the IEP effectively. According to Vaz et al (2015), one of the factors that can influence the attitude practiced by a teacher is self-efficacy in educating SEN children.…”
Section: Discussionmentioning
confidence: 99%
“…Since the affective factor is the driving force for the learning process (Kasap & Peterson, 2018;Kasap, 2021), teachers should adopt a positive attitude towards the IEP implementation process so that the IEP can be implemented effectively. The findings of this study have shown that special education teachers face the biggest challenge in terms of attitude.…”
Section: Discussionmentioning
confidence: 99%
“…Prenger & Schildkamp (2018) state that teachers with the enthuasiasm and intention can bring better IEP implementation results for LD students because they often hold positive beliefs about the IEP practices that have been implemented. In order to ensure that the effectiveness of IEP process, special education teachers should be always positive towards all the IEP implementation processes (Kasap & Peterson, 2018;Kasap, 2021). Therefore, it is important to identify the attitude of special education teachers in Malaysia towards the IEP implementation process.…”
Section: Introductionmentioning
confidence: 99%